Low-Complexity One-Step Digital Back-Propagation for Single Span High-Capacity Coherent Transmissions - Xingyu Zhou; Qunbi Zhuge; Meng Qiu; Fangyuan Zhang; Mohammed Sowailem; Thang M. Hoang; Meng Xiang; Baojian Wu; Kun Qiu; David V. Plant (IEEE Photonics Journal, 2017)
A low-complexity one-step digital back-propagation (DBP) scheme is proposed to mitigate intrachannel and interchannel fiber nonlinearities in high-capacity single span transmissions. Compared with conventional coherent receivers, the only additional calculation is a low-complexity nonlinear phase noise compensation stage operated between bulk chromatic dispersion (CD) compensation and adaptive equalizer. The required number of real additions and multiplications per sample are only (6N + 2) and (2N + 6), respectively, where N is the number of compensated wavelength-division-multiplexing (WDM) channels. With the proposed one-step DBP, we demonstrate that the nonlinear noise can be suppressed by >60% in single channel experiments and >40% in seven-channel WDM simulations.